Strain effects on halide perovskite solar cells. (5th August 2022) - Yang, Bowen; Bogachuk, Dmitry; Suo, Jiajia; Wagner, Lukas; Kim, Hobeom; Lim, Jaekeun; Hinsch, Andreas; Boschloo, Gerrit; Nazeeruddin, Mohammad Khaja; Hagfeldt, Anders
Abstract : This review systematically describes the origins, characterization and implications of strain in perovskite solar cells and proposes novel control strategies. Abstract : Halide perovskite solar cells (PSCs) have achieved power conversion efficiencies (PCEs) approaching 26%, however, the stability issue hinders their commercialization. Due to the soft ionic nature of perovskite materials, the strain effect on perovskite films has been recently recognized as one of the key factors that affects their opto-electronic properties and the device stability. Herein, we summarized the origins of strain, characterization techniques, and implications of strain on both perovskite film and solar cells as well as various strategies to control the strain. Finally, we proposed effective strategies for future strain engineering. We believe this comprehensive review could further facilitate researchers with a deeper understanding of strain effect and enhance the research activity in engineering the strain to further improve performance and especially the device stability toward commercialization.